LINC00641/miR-4262/NRGN axis confines cell proliferation in glioma. Issue 8 (2nd August 2020) - Yang, Jinghui; Yu, Duo; Liu, Xueshibojie; Changyong, E.; Yu, Shan
ABSTRACT: Glioma is the most prevalent brain malignancy with high mortality. In recent decades, the regulatory role of long noncoding RNAs (lncRNAs) has been unmasked in glioma. In this study, we focused on the function and mechanism of LINC00641 in glioma. First of all, we found that LINC00641 was expressed at a low level in glioma cell lines. Importantly, overexpression of LINC00641 prevented cell proliferation but enhanced cell apoptosis. Meanwhile, NRGN, a previously-reported downregulated mRNA in GBM, was disclosed as a tumor suppressor in glioma cells. Besides, we verified that NRGN could be positively regulated by LINC00641 in glioma cells. Moreover, the cellular distribution of LINC00641 was identified to be cytoplasmic. Therefore, bioinformatics analysis and mechanism experiments were carried out and we determined that miR-4262 was the shared miRNA between LINC00641 and NRGN. In contrast to LINC00641 and NRGN, miR-4262 was dramatically upregulated in glioma cells. Furthermore, we confirmed that LINC00641 acted as a ceRNA in glioma cells via absorbing miR-4262 to upregulate NRGN. More importantly, silenced NRGN countervailed the repression on glioma cell proliferation caused by LINC00641 upregulation. Collectively, our findings unveiled that LINC00641 serves as a tumor inhibitor in glioma by targeting miR-4262/NRGN axis, providing a new potential therapeutic target for glioma patients.